Development of culture village through service quality analysis to customer satisfaction - Sumartini, Ade Ruly; Idawati, Ida Ayu Agung (International research journal of management, IT and social sciences, 2020)
Cities tend to be the focus of development, including the development of the tourism sector. This tendency is motivated by the social demographic factors of the population of the city is much easier to accept the latest issues related to modernization and economic empowerment. Denpasar, as the center of the city, still has green and beautiful land, which is Kertalangu Cultural Village. As a tourist destination, there are many facilities and infrastructures in Kertalangu Cultural Village needs to be improved. The purpose of this research is to find out and provide empirical evidence about the Development of Kertalangu Cultural Village Based on Analysis of Service Quality on Customer Satisfaction. The data collection method uses a questionnaire distributed to 100 respondents. Data analysis techniques used multiple regression analysis using mixed methods, both qualitatively and quantitatively. The results showed that service quality variables such as responsiveness, assurance, empathy, and reliability had a positive and significant effect on customer satisfaction. The service quality variable in the form of tangible (physical evidence) has a positive effect but not significant.